DEVELOPING STUDENT VOCABULARY WORKSHEET BY USING AFFIXES - Pradita, Intan; Sadiq, Nizamudin (Universitas Ahmad Dahlan, 2016)
This paper aims at describing the stages of developing vocabulary worksheet by using affixes by adopting the process of the same development research of Wutsqo. The stages of vocabulary worksheet development involved the needs analysis, the making of the vocabulary worksheet, the validation process by the reviewer, the make up of the first design based on the feedback by the reviewer, and the try out. the object of this studyÂ was the students of Grammar for English Teacher class of the academic year 2014/2015. The instruments of this study were pre-test as the initial needs analysis of the students capability of vocabulary stock that they had. The second instrument was the previous research data that was conducted by the researchers to identify how necessary to develop an effective vocabulary learning. The third instrument were three two of questionaires. The first one was for the reviewer to validate the first design of the worksheet and to ask for the feedback, and the second one was for the students in order to identify their personal impression towards the worksheet. The results of this study are; 1) Based on the assessment validator can be concluded that the aspect of validity has met the criteria development vocabualry student worksheet to learn the material additive that has been prepared to have a very good quality, 2) Based on the recommendation of experts and providers of materials, practicality aspect has fulfilled the minimum criteria with certain notes on 21st century learning, 3) The results of the pre-test and post-test student learning augmentation material by using SVW has met the minimum criteria of improvement.